Comprehensive Review of Epidemiology and Treatment of Snakebite Envenomation in West Africa: Case of Benin - Ayékotchami Jacques Dossou; Adandé Belarmain Fandohan; Timothy Omara; Jean-Philippe Chippaux (Journal of Tropical Medicine, 2024)
Snakebite envenomation (SBE) constitutes a public health, social, and economic problem affecting poor communities in intertropical and subtropical regions. This review sought to synthesize literature on snakebite envenomation in Benin to highlight research perspectives and strategies for better management of the menace. A literature search performed in multidisciplinary electronic databases showed that the prevalence of SBE is high in Benin, but the incidences, associated morbidities, and mortalities are greatly underestimated. Most snake envenomations are by Echis ocellatus in Northern Benin during the rainy season. Adults involved in agricultural activities are the most affected. The absence of antivenin serum in the most affected areas explains the preference for alternative and traditional medicine as the first-line treatment for SBE in Benin. In conclusion, it would be imperative to revitalize the snakebite reporting system in order to have better epidemiological data and to develop a sustainable national strategy for the control and management of snakebite envenomation.